2015
DOI: 10.1158/0008-5472.can-15-0989
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Independent EGFR Signaling

Abstract: Constitutive activation of the EGFR is common in cancer due to EGFR wild type (EGFRwt) overexpression or the presence of mutant EGFR. Signaling by constitutively active NSCLC EGFR mutants or the EGFRvIII mutant in glioblastoma has been studied intensively and the downstream signals are known. Normally, the EGFRwt is activated when it is exposed to ligand resulting in activation of canonical signals such as ERK and Akt. The EGFRwt also becomes tyrosine phosphorylated and constitutively activated without ligand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
142
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(149 citation statements)
references
References 48 publications
7
142
0
Order By: Relevance
“…Natural ligands of EGFR are growth factors, including EGF and TGF-a [26,27]. Ligand binding results in receptor phosphorylation and activation, although ligandindependent and constitutive EGFR signalling have also been described [28,29]. EGFR activation steers among others JAK/STAT signalling as well as the PI3K/ AKT, the RAS/RAF/ERK and the PLC/PKC pathways controlling processes including DNA repair, proliferation, angiogenesis, and inhibition of apoptosis [30].…”
Section: Introductionmentioning
confidence: 99%
“…Natural ligands of EGFR are growth factors, including EGF and TGF-a [26,27]. Ligand binding results in receptor phosphorylation and activation, although ligandindependent and constitutive EGFR signalling have also been described [28,29]. EGFR activation steers among others JAK/STAT signalling as well as the PI3K/ AKT, the RAS/RAF/ERK and the PLC/PKC pathways controlling processes including DNA repair, proliferation, angiogenesis, and inhibition of apoptosis [30].…”
Section: Introductionmentioning
confidence: 99%
“…EGFR variant III is a tumor specific mutation that is widely expressed in GBM and other neoplasms (Sampson et al, 2008; Guo et al, 2015). This mutation encodes a constitutively active tyrosine kinase that is reported to be associated with tumorigenicity and cellular resistance to chemotherapeutic agents or radiation.…”
Section: Cellular Immune Responses To Mutated Egfrmentioning
confidence: 99%
“…In addition, oncogenic somatic mutations in specific sites of the EGFR gene, such as EGFR variant III (EGFRvIII) in glioblastoma multiforme (GBM) and activating EGFR mutations in non-small cell lung cancer (NSCLC), have been reported to be closely associated with tumorigenesis (Guo et al, 2015; Tan et al, 2015). Since EGFR is overexpressed in various types of epithelial cancers, including pancreatic, colorectal, breast, and lung cancer, it has been suggested that EGFR might be an appropriate target for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…These aberrant proteins may have a decreased activity or maintain a constitutive activation. 3,17,[27][28][29][30] The mutated variant, known as EGFR variant III (EGFRvIII ), encoded by EGFRvIII, has a deletion of exons 2-7, which encode the extracellular domain of ligand binding. The altered protein is constitutively active with slow degradation, allowing more time to interact with its ligand.…”
mentioning
confidence: 99%
“…EGFRvIII has been associated with increased tumor cell proliferation in mouse model and it has been observed that its presence is associated with a lower response to treatment with radiation therapy. 3,16,30,31 McItyre et al 3 studied the expression of EGFRvIII in OSCC, noting that this is overexpressed in 2% of patients. Melchers et al 31 analyzed 531 cases of HNC and found no difference in the prevalence of the mutation compared to healthy controls.…”
mentioning
confidence: 99%